Isolated Knee Arthritis as Early and Only Symptom of Whipple’s Disease - Dario Giunchi; Natalie Marcoli; Luca Deabate; Marco Delcogliano; Enrique Testa; Christian Candrian; Paolo Gaffurini (Case Reports in Medicine)
We report a case of isolated Whipple’s disease involving the knee of a 64-year-old female patient who presented recurrent monoarthritis whose origin was not clear. Initially, the cause of the gradually invalidating symptoms was related to a meniscal lesion and a diffuse minor grade chondropathy, but pain and functional impairment suggested that more exams were needed. Biopsies were performed during arthroscopy. The histology showed highly inflammatory infiltrates with PAS staining negative for Tropheryma while PCR revealed the infection with Tropheryma whipplei. This, following the recommendation of a rheumatologist and infectious disease specialist, led to biopsies of the gastrointestinal tract and analysis of the cerebrospinal fluid that showed no other organ involvement. This confirms the scientific literature that an isolated monoarthritis without involvement of the gastrointestinal tract caused by this bacterium is rare but can occur as an early manifestation of potentially fatal systemic disease. Moreover, a review of the scientific literature showed the uncertainty about epidemiology of this rare disease, suggesting that more and specific data are required.